Indications and outcome of surgery for pulmonary aspergilloma. Issue 9 (September 1997) - el Oakley, R; Petrou, M; Goldstraw, P
Abstract : BACKGROUND: The indications and the outcome of surgery for pulmonary aspergilloma remain highly controversial. The short term and long term results of lung resection or cavernostomy in 24 patients with pulmonary aspergilloma are reported. METHODS: The case notes of 27 consecutive patients referred for surgical assessment for pulmonary aspergilloma at the Royal Brompton Hospital over the last 14 years were reviewed. Patients were categorised into four classes according to their fitness for lung resection and the severity of their symptoms. Severe symptoms were defined as life threatening haemoptysis or other symptoms requiring more than one hospital admission. Class I (n = 1), fit individual with mild or no symptoms; class II (n = 17), fit individuals with severe symptoms; class III (n = 1), unfit individual with no symptoms; and class IV (n = 8), unfit individuals with severe symptoms. Two asymptomatic patients and one on an IVOX pump were not accepted for surgery. Lung resection was performed in all 17 patients with class II disease, comprising segmentectomy only in five patients, lobectomy and segmentectomy in seven, and a completion pneumonectomy in five patients. Cavernostomy was performed in seven patients with class IV disease. RESULTS: Surgery was often complicated by prolonged air leakage and infection of residual space. There was no operative mortality in the group treated by resection whereas two of those who underwent cavernostomy died in the early postoperative period. All survivors were followed up for a median of 17 months (range 1-72 months); 19 were alive and had no symptoms attributable to aspergilloma. Late recurrence occurred in two patients in the cavernostomy group. The only late death occurred in the resection group five months postoperatively and was attributed to end stage renal disease. CONCLUSIONS: Lung resection in selected patients with complicated aspergilloma can be performed with low operative mortality. Cavernostomy is associated with high mortality and morbidity and should therefore only be performed in patients with life threatening symptoms who are unfit for lung resection.